PENGARUH PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN DAN RASIO LANCAR TERHADAP RETURN ON ASSETS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Muhammad Zain Satria Atmaja; Dul Muid (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of accounts receivable turnover, inventory turnover and current ratio on ROA. The variables used in the test are accounts receivable turnover, inventory turnover and current ratio as independent variables, and ROA as the dependent variable.            This study uses a manufacturing company from 2017 to 2019 with a total sample of 138 samples. Sampling is based on a purposive sampling method that follows certain criteria. Multiple linear regression analysis is a method of analysis used in research.            The results showed that inventory turnover and current ratio had a positive and significant effect on ROA. Meanwhile, accounts receivable turnover has a negative but insignificant effect on ROA.